Cardiohemodynamic indices changes in students during the computer lesson (One Health & Risk Management, 2021)
Introduction. Education and training, free time and the rest of children and adolescents in the current conditions are impossible without new information technologies, primarily computer technologies. The computer is a means, which provides feedback in the learning process, individualizing the learning process, allows searching for information from a large number of sources, modelling the processes or phenomena studied, organizing collective work and in groups. Parallel with the advantages of using computers in the instructional-educational process, they also have a negative influence on the body if they are not used correctly. Research shows that in the computer training process is registered fatigue, emotional disorders, posture disorders, severe neuromascular disorders, osteoarticular, cardiovascular disorders, carpal tunnel syndrome, computer vision sindrom, computer is an important risk factor for obesity.Material and methods. A cross-sectional epidemiological research was initiated. The research was conducted on 123 students, including 52 boys and 71 girls. Pulse (beats/min.) and blood pressure (mm Hg) measurements were made in 10 classes (grades 5-9) at the beginning and end of the computer lesson. Using the obtained data, the following indices were calculated: pulsatile voltage (mm Hg), average dynamic voltage (mm Hg), systolic volume (mL), Minute-heart volume (L/ min.). The students, together with the computer science teacher, signed an agreement to take the measurements.Results. The pulse rate in the studied group of students at the beginning of the computer lesson, constituted values between 70 and 86 beats/min., with an average value of 77.6±3.1 beats/min., and at the end of the lesson it decreased, constituting values between 66 and 83 beats/min., with an average value of 75.8±3.7 beats/min. (p
Keywords: cardio-hemodynamic indices; students; computer lesson; pulse; blood pressure.